Improving the moisture resistance of adobe structures - Heredia Zavoni, Ernesto A. (1987)
Mud plasters or stuccos are commonly used to improve the moisture resistance of adobe structures. This study presents the results of a durability test program on mud plasters subjected to simulated rain. Different stabilizers were used, such as extracts from tuna leaves (a variety of cactus plants), banana leaves and stalks, locust bean tree pods, and manure. Test results of mud plasters stabilized with asphalt are presented for comparison. Experimental results showed that drying shrinkage cracking is one of the most important factors affecting the disintegration of soil stuccos. A procedure was developed to obtain a crack-resistant stucco composed of natural soil, coarse sand, straw, and a stabilizer extracted from the cactus plant. The stucco was found to be water-resistant.